2021
DOI: 10.1029/2020jd032787
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced MOD16 Evapotranspiration Model for the Tibetan Plateau During the Unfrozen Season

Abstract: Evapotranspiration (ET) is composed of soil evaporation (ETs), canopy transpiration (ETc), and canopy intercepted water evaporation (ETw), and it plays an indispensable role in the water and energy cycles of land surface processes. More accurate estimations of variations in ET are essential for natural hazard monitoring and water resource management. An improved algorithm for ETs with soil moisture and texture (SMT) and an optimized ETc based on the MOD16 model (MOD16‐STM) are proposed for the cold, arid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 158 publications
0
19
0
Order By: Relevance
“…Here, we compared estimation results of monthly E by five CR-based models in the present study with the latest two improved remote-sensing ET models that have been validated for the QTP. One is an improved MOD16 model by Yuan [71], referred to as "MOD16_Yuan" in this study; the another one is an improved SEBS model by Han [72], referred to as "SEBS_Han" in this study. Both obtained better accuracy with in situ measurements than that in previous results.…”
Section: Comparison With Previous Studies On the Qtp At A Single Poin...mentioning
confidence: 99%
“…Here, we compared estimation results of monthly E by five CR-based models in the present study with the latest two improved remote-sensing ET models that have been validated for the QTP. One is an improved MOD16 model by Yuan [71], referred to as "MOD16_Yuan" in this study; the another one is an improved SEBS model by Han [72], referred to as "SEBS_Han" in this study. Both obtained better accuracy with in situ measurements than that in previous results.…”
Section: Comparison With Previous Studies On the Qtp At A Single Poin...mentioning
confidence: 99%
“…Through optimizing multiple physical parameters (surface resistance of bare soil, and aerodynamic resistance of soil surface, and the mean potential stomatal conductance per unit leaf area index, and so on), the RMSEs of the ET values derived at the five sites were enhanced compared to those obtained using the original MOD16 model and the SWI‐PT. Although the optimized MOD16 model showed a more stable performance than the other models with regards to the ET estimation bias, ET uncertainties still exist over the TP due to uncertainties in other physical parameters (Yuan et al., 2021). Other studies have reported similar findings.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these uncertainties in estimated ET values over the TP, several studies have focused on improving the ET simulation and prediction abilities over the TP by tuning the models used to describe physical processes and their physical parameters. For example, Yuan et al (2021) employed an improved MOD16 model, original called the MOD16 model, and a soil water index-based PT algorithm (SWI-PT) to evaluate ET at five sites over the TP. Through optimizing multiple physical parameters (surface resistance of bare soil, and aerodynamic resistance of soil surface, and the mean potential stomatal conductance per unit leaf area index, and so on), the RMSEs of the ET values derived at the five sites were enhanced compared to those obtained using the original MOD16 model and the SWI-PT.…”
mentioning
confidence: 99%
“…Thus, accurately estimating ET is necessary for better quantification and allocation of water resources, which is of great significance to the sustainable utilization and management of global water resources in an era of growing climate change. Generally, the Penman-Monteith (PM) algorithm and the Priestley-Taylor (PT) algorithm are the two most commonly used methods for estimating ET, though the two algorithms have been proposed for more than four decades [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been conducted to improve the PM algorithm from different aspects, such as stomatal conductance [7], soil moisture [10], temperature difference between day and night [7,10,11], etc. However, to date, accurate estimation of actual ET at regional scales is still challenging [12].…”
Section: Introductionmentioning
confidence: 99%